2015
DOI: 10.5007/2175-7968.2015v35nesp2p78
|View full text |Cite
|
Sign up to set email alerts
|

Da formação comunitária à formação universitária (e vice e versa): novo perfil dos tradutores e intérpretes de língua de sinais no contexto brasileiro

Abstract: Neste artigo, objetiva-se realizar uma discussão sobre o novo perfil de tradutores e intérpretes de língua de sinais que está se constituindo no Brasil a partir das políticas públicas de incentivo à formação deste profissional. Analisa-se, qualitativamente, um questionário semiaberto respondido por alunos de um curso de Bacharelado em Tradução e Interpretação em Libras e Língua Portuguesa de uma universidade federal localizada no Estado de São Paulo. Os resultados apontam para uma busca pela área não mais marc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
10

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 7 publications
0
3
0
10
Order By: Relevance
“…According to the results, it was observed that, although no difference was identified between G1 and G2 regarding the status of completion for their higher education, differences were evident between the groups in the areas of their specialization, and as highlighted in previous studies (1,2,6) , also evident in the participants' age, time of professional practice, sex, education, type of education in LIBRAS, and type of education in translation and interpretation (Table 1). Despite the statistical differences evident between the participant cohort groups, there is potential to reflect and foster further research on speech intelligibility with respect to professional interpreters who have no academic education, or specialization.…”
Section: Discussionmentioning
confidence: 80%
See 2 more Smart Citations
“…According to the results, it was observed that, although no difference was identified between G1 and G2 regarding the status of completion for their higher education, differences were evident between the groups in the areas of their specialization, and as highlighted in previous studies (1,2,6) , also evident in the participants' age, time of professional practice, sex, education, type of education in LIBRAS, and type of education in translation and interpretation (Table 1). Despite the statistical differences evident between the participant cohort groups, there is potential to reflect and foster further research on speech intelligibility with respect to professional interpreters who have no academic education, or specialization.…”
Section: Discussionmentioning
confidence: 80%
“…Deaf people, who are users of Brazilian Sign Language, have expanded their work-related activities and increased their representation in society, thereby legitimizing the recognition of sign language as an official language. As indicated by literature reviews of linguistic studies (2,15,18) , this has led to the progressive development of the Sign Language Interpreter (SLI), which is a new labor market force centered on ensuring communication accessibility to these various spheres (6) . Recently in Brazil, legislation has further structured this process, conferring legitimacy to the profession of SLI and LIBRAS as a legal and recognized language in the country (19,20,21) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Esse curso tem como objetivo aperfeiçoar e formar tradutores e intérpretes que possuem outras formações de base, mas que atuam com a tradução e com a interpretação do par Libras/LP. Tendo em vista o deslocamento sócio-histórico de TILS das esferas religiosas, familiares e comunitárias para as esferas profissionais, muitos trabalhadores do campo possuem formação em áreas diversas como Letras, Pedagogia, Fonoaudiologia, Educação Especial, Administração, Enfermagem dentre outras (NASCIMENTO, 2016;MARTINS & NASCIMENTO, 2015). Em alguns casos, essas formações, principalmente as relacionadas às humanidades, foram motivadas pela relação e convivência com as pessoas surdas.…”
Section: Contexto De Coleta Do Corpusunclassified
“…pedagógica presente nas variadas salas de aula com intérpretes educacionais(MARTINS, 2013) v .O tema anunciado, do TILSE, é relevante pela crescente proposta de formação em nível de graduação, com a abertura dos cursos em Letras Libras/Bacharelado, proposto pelas universidades federais, como resposta aos incentivos públicos de verbas governamentais, e frente a essa nova realidade, há a necessidade de ajustes e reflexões sobre o currículo desenhado nas diferentes instituições de ensino superior (IES) no Brasil(MARTINS & NASCIMENTO, 2015). Como apontaLima (2006) a interpretação em contexto educacional inicia-se sem uma formação prévia e com isso várias consequências são percebidas, como o não domínio da língua de sinais, pouco ou nenhum conhecimento das questões pedagógicas que envolvem alunos surdos, e tudo isso pode levar a uma atividade que, em última instância, prejudica o aluno surdo.…”
unclassified